Kvantitativna glosa o kompliciranosti in kompleksnosti gospodarskih kaznivih dejanj - Keršmanc, Ciril (Revija za kriminalistiko in kriminologijo, 2013)
The serious crimes of "Business fraud" and "Abuse of position or trust in business" as they are defined in the Slovene Penal code, are the two central legal constructs in prosecuting economic crime in Slovenia. This article tries to point out the differences between the two and aims to do this, not via an abstract analysis of the norms themselves, but by using quantitative data. In terms of the number of criminal complaints being processed in the category of economic crimes, "Business fraud" has the highest frequency, while "Abuse of position or trust in business" trails far behind. However, despite the relatively lower frequency, it is estimated that "Abuse of position or trust in business" cumulatively causes the most damage/illegal gain in the group of so called economic (serious) crimes in Slovenia. Outlined he re are other quantitative differences between the two categories on two different leveis. Firstly, the general statistics collected by the Slovenian Ministry of Internal Affairs are aggregated into an original graphical representation of the most basic numerical relationships. Secondly, the results of the fieldwork research that was conducted at the Ljubljana District Prosecutor's Office in which 1255 cases were analysed are presented. Both serious crimes were included in the sample and the results are analysed and compared in the following categories: the number of suspects/per crime, the length of the procedure/per crime, the number of guilty verdicts in cases where the prosecutor filed the indictment and finally the amount of (estimated) illegal gain/per crime. In conclusion, the author synthesises his quantitative findings with his qualitative observations and presents a model according to which difficult economic crime cases are divided into two categories, namely complex cases (these are more often found among the cases of "Abuse of position or trust in business") and complicated cases (these are more often found among the cases of "Business fraud"). The article closes by noting that in reality, prosecutors and investigative bodies have to deal with an "untidy" mixture of complex and complicated cases which need to be reduced to a more manageable level, if we wish to limit economic crime more effectively. This is where, in a system governed by the so called legality principle of prosecuting serious crimes, interpretative discretion and the imagination of investigative and prosecutorial bodies comes into play.
Keywords: abuse of position; business fraud; economic crime; gospodarska dejavnost; gospodarska kriminaliteta; interpretative discretion; interpretativna diskrecija; legalitetno načelo; legality principle; limiting economic crime; obvladovanje gospodarske kriminalitete; poslovna goljufija; zloraba položaja